Micro Arrum Product Marketing Strategy Implementation in Attracting the Interest of Luwu Branch Sharia Payment Customers' Interest During Covid-19 - Andi Nurfaika Muslim (Program Studi Perbankan Syariah, IAIN Palopo, 2022)
This study aims to describe the marketing strategy for arrum micro products in attracting the interest of customers of the Luwu branch of Islamic Pawnshops during the Covid-19 pandemic. This type of research is a descriptive qualitative approach. The research data were obtained from primary data sources using data collection techniques, namely observation, interviews and documentation. Furthermore, this research data was analyzed by data reduction, data presentation and conclusion drawing/data verification. As for testing the validity of the data using triangulation. The results showed that the marketing strategy for arrum micro products implemented by the Luwu branch of sharia pawnshops through 4P was: Product Strategy, by making products according to customer needs, developing rahn products into arrum and providing good service. The Price Strategy, the Luwu branch of Islamic pawnshops provides lower mu'nah or capital leases compared to other financing. Promotion strategy, by becoming sponsorship, through canvassing, distributing brochures, door to door, through the internet such as whatsaap, wa blast, Instagram, Facebook, Bukalapak and other social media. StrategiPlace, the location of the sharia pawnshop is in the center of the crowd close to the Andi Tadda traditional market, in the city center and on the edge of the main road.